2021
DOI: 10.1038/s41598-021-92479-3
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami detection by GPS-derived ionospheric total electron content

Abstract: To unravel the relationship between earthquake and tsunami using ionospheric total electron content (TEC) changes, we analyzed two Chilean tsunamigenic subduction earthquakes: the 2014 Pisagua Mw 8.1 and the 2015 Illapel Mw 8.3. During the Pisagua earthquake, the TEC changes were detected at the GPS sites located to the north and south of the earthquake epicenter, whereas during the Illapel earthquake, we registered the changes only in the northward direction. Tide-gauge sites mimicked the propagation directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 79 publications
3
17
0
Order By: Relevance
“…(2015) and Shrivastava et al. (2021) for the 1 April 2014 earthquake (Figure 4c); by Reddy et al. (2016) and Shrivastava et al.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…(2015) and Shrivastava et al. (2021) for the 1 April 2014 earthquake (Figure 4c); by Reddy et al. (2016) and Shrivastava et al.…”
Section: Discussionmentioning
confidence: 82%
“…(2016) and Shrivastava et al. (2021) for the 16 September 2015 earthquake (Figures 3, 7a, and 7b); and by Shults et al. (2016) and X. Liu et al.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Their technique has been implemented at several GNSS-receivers around the Pacific Ocean (https://iono2la.gdgps.net), and is aiming -in the future -to detect traveling ionospheric disturbances (TIDs) associated with tsunamis. Shrivastava et al [23] demonstrated the possibility of tsunami detection by GPS-derived TEC, however, no discussion on the real-time use was provided.…”
Section: Introductionmentioning
confidence: 99%